Targeted long-read sequencing reveals clonally expanded HBV-associated chromosomal translocations in patients with chronic hepatitis B - van Buuren, Nicholas; Ramirez, Ricardo; Soulette, Cameron; Suri, Vithika; Han, Dong; May, Lindsey; Turner, Scott; Parvangada, P.C.; Martin, Ross; Chan, Henry L.Y.; Marcellin, Patrick; Buti, Maria; et al. (JHEP reports, 2022)
HBV infects over 257 million people worldwide and is associated with the development of hepatocellular carcinoma (HCC). Integration of HBV DNA into the host genome is likely a key driver of HCC oncogenesis. Here, we utilise targeted long-read sequencing to determine the structure of HBV DNA integrations as well as full isoform information of HBV mRNA with more accurate quantification than traditional next generation sequencing platforms. DNA and RNA were isolated from fresh frozen liver biopsies collected within the GS-US-174-0149 clinical trial. A pan-genotypic panel of biotinylated oligos was developed to enrich for HBV sequences from sheared genomic DNA (∼7 kb) and full-length cDNA libraries from poly-adenylated RNA. Samples were sequenced on the PacBio long-read platform and analysed using a custom bioinformatic pipeline. HBV-targeted long-read DNA sequencing generated high coverage data spanning entire integrations. Strikingly, in 13 of 42 samples (31%) we were able to detect HBV sequences flanked by 2 different chromosomes, indicating a chromosomal translocation associated with HBV integration. Chromosomal translocations were unique to each biopsy sample, suggesting that each originated randomly, and in some cases had evidence of clonal expansion. Using targeted long-read RNA sequencing, we determined that upwards of 95% of all HBV transcripts in patients who are HBeAg-positive originate from cccDNA. In contrast, patients who are HBeAg-negative expressed mostly HBsAg from integrations. Targeted lso-Seq allowed for accurate quantitation of the HBV transcriptome and assignment of transcripts to either cccDNA or integration origins. The existence of multiple unique HBV-associated inter-chromosomal translocations in non-HCC CHB patient liver biopsies suggests a novel mechanism with mutagenic potential that may contribute to progression to HCC. Fresh frozen liver biopsies from patients infected with HBV were subjected to targeted long-read RNA and DNA sequencing. Long-read RNA sequencing captures entire HBV transcripts in a single read, allowing for resolution of overlapping transcripts from the HBV genome. This resolution allowed us to quantify the burden of transcription from integrations vs. cccDNA origin in individual patients. Patients who were HBeAg-positive had a significantly larger fraction of the HBV transcriptome originating from cccDNA compared with those who were HBeAg-negative. Long-read DNA sequencing captured entire integrated HBV sequences including multiple kilobases of flanking host sequence within single reads. This resolution allowed us to describe integration events flanked by 2 different host chromosomes, indicating that integrated HBV DNA are associated with inter-chromosomal translocations. This may lead to significant transcriptional dysregulation and drive progression to HCC. [Display omitted] •Fresh frozen liver biopsies from patients with CHB were subjected to targeted long-read RNA and DNA sequencing.•Inter-chromosomal translocations associated with HBV integration events detected in one-third of patients.•Chromosomal translocations were unique to each biopsy sample, suggesting that each originated randomly.•A larger fraction of the HBV transcriptome originates from cccDNA in patients who are HBeAg-positive.